DESIGN OF DRAWING BOOK AS A VEGETATION INTRODUCTION MEDIA FOR CHILDREN - Widyastuti, Herlina (Arty: Jurnal Seni Rupa, 2020)
Children have an important role as the nation's next generation who will take part in protecting and building environmental sustainability. Expected later this knowledge grew into a good habit of his mature later. Through the science of visual communication design, the authors provide an alternative learning tool for children in the field of plant science to develop the children's understanding of the plant through an illustrated book with the title "Knowing and Understanding Plants." The picture book is divided into two series; series of classes 1, 2, 3 and series of classes 4, 5, 6. The process of designing a picture book is completed with digital techniques using Adobe Photoshop software. This design process through several stages of working process are the processes of pre-productions, production and post-production processes. All illustrations arranged in picture books are a representation of the plant science material. All the work is assessed through the specifications, description, and analysis. Judging from the results of the analysis in terms of aesthetic and illustrative, works of this picture book has a communicative appearance in plant science through realist style illustrations with a touch of cheerful and decorative characteristics. In a communication analysis, this work represents the science clearly. Through the design of this picture book, is expected to support and inspire children in the study of plant